Handbook of Research on Smart Management for Digital Transformation - Barbosa, Belem (IGI Global, 2022)
In a global and digital society, businesses are constantly being challenged by innovative and disruptive management strategies. The dramatic changes that took place in all corners of the world during the COVID-19 pandemic confirmed that companies need to update their resources and anticipate trends. The current changes introduced by digitalization offer endless innovation scenarios and strategic opportunities to companies but also demand an accurate and structured analysis of drivers, motivations, and determinants for success in this transformation. The Handbook of Research on Smart Management.